2009
DOI: 10.1093/intimm/dxp052
|View full text |Cite
|
Sign up to set email alerts
|

Activation of invariant NKT cells confers protection against Chlamydia trachomatis-induced arthritis

Abstract: The role of invariant NKT (iNKT) cells in reactive arthritis is unknown. We explored the functional role of NKT cells in reactive arthritis using an established murine model of Chlamydia trachomatis-induced arthritis (CtIA). CtIA in wild-type and CD1d knockout (KO) mice was induced by intra-articular injection of C. trachomatis. The effect of alpha-galactosylceramide (alpha-GalCer) activation of iNKT cells was investigated by intra-peritoneal administration of alpha-GalCer. Histopathological and phenotypic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…CD1d-restricted NKT cells played a protective role in host defense against infection by some bacterial pathogens such as Mycobacterium tuberculosis and Pseudomonas aeruginosa [9,10], but the presence of these cells was detrimental in the case of Salmonella and Listeria infections [11,12]. In the case of chlamydial infections, CD1d-restricted NKT cells conferred protection against C. tracho-matis -induced arthritis [13], or C. muridarum -induced genital tract infection [14]; but Bilenki et al [15] have shown, conversely, that CD1d-restricted NKT cells promote C. muridarum lung infection. Moreover, using another chlamydial species, Chlamydophila pneumoniae , Joyee et al [16] reported that CD1d-restricted NKT cells play a crucial role in mediating the protective immune responses against lung infection.…”
Section: Introductionmentioning
confidence: 99%
“…CD1d-restricted NKT cells played a protective role in host defense against infection by some bacterial pathogens such as Mycobacterium tuberculosis and Pseudomonas aeruginosa [9,10], but the presence of these cells was detrimental in the case of Salmonella and Listeria infections [11,12]. In the case of chlamydial infections, CD1d-restricted NKT cells conferred protection against C. tracho-matis -induced arthritis [13], or C. muridarum -induced genital tract infection [14]; but Bilenki et al [15] have shown, conversely, that CD1d-restricted NKT cells promote C. muridarum lung infection. Moreover, using another chlamydial species, Chlamydophila pneumoniae , Joyee et al [16] reported that CD1d-restricted NKT cells play a crucial role in mediating the protective immune responses against lung infection.…”
Section: Introductionmentioning
confidence: 99%
“…A similar Th1-biasing role for NKT cells involving DCs has been established in a murine infection model of Chlamydia pneumoniae [36]. Besides aiding Chlamydial clearance in mice, NKT cells have also been reported to have a protective role in Chlamydia trachomatis -induced arthritis [37]. CD1d −/− mice, which completely lack NKT cells, showed poor local bacterial clearance in the joint and more severe arthritis as compared to wild type controls.…”
Section: Bacterial Infectionsmentioning
confidence: 73%
“…113 Additionally, in another infection-triggered form of arthritis, induced by Chlamydia trachomatis, iNKT cells are thought to have a protective role. 114 These studies suggest that iNKT cells have a non redundant role in regulating forms of infection-triggered arthritis and their extra-articular manifestations.…”
Section: Rheumatoid Arthritismentioning
confidence: 98%